A novel tyrosine kinase inhibitor AMN107 (nilotinib) normalizes striatal motor behaviors in a mouse model of Parkinson’s disease - Tanabe, Akie; Yamamura, Yukio; Kasahara, Jiro; Morigaki, Ryoma; Kaji, Ryuji; Goto, Satoshi (Frontiers in Cellular Neuroscience, 2014)
Abnormal motor behaviors in Parkinson’s disease (PD) result from striatal dysfunction due to an imbalance between dopamine and glutamate transmissions that are integrated by dopamine- and cAMP-regulated phosphoprotein of 32 kDa (DARPP-32). c-Abelson tyrosine kinase (c-Abl) phosphorylates cyclin-dependent kinase 5 (Cdk5) at Tyr15 to increase the activity of Cdk5, which reduces the efficacy of dopaminergic signaling by phosphorylating DARPP-32 at Thr75 in the striatum. Here, we report that in the mouse striatum, a novel c-Abl inhibitor, nilotinib (AMN107), inhibits phosphorylation of both Cdk5 at Tyr15 and DARPP-32 at Thr75, which is negatively regulated by dopamine receptor activation through a D2 receptor-mediated mechanism. Like a D2-agonist, nilotinib synergizes with a D1-agonist for inducing striatal c-Fos expression. Moreover, systemic administration of nilotinib normalizes striatal motor behaviors in a mouse model of PD induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). These findings suggest that nilotinib could possibly serve as a new and alternative agent for treating PD motor symptoms.